Sensing the Worst: Neurophenomenological Perspectives on Neutral Stimuli Misperception in Schizophrenia Spectrum - Sestito, Mariateresa; Parnas, Josef; Maggini, Carlo; Gallese, Vittorio (Frontiers in Human Neuroscience, 2017)
While investigating social cognitive impairments in schizophrenia, prominent evidence has been found that patients with schizophrenia show a tendency to misclassify neutral stimuli as negatively valenced. Within this population, patients presenting delusions are more prone this phenomenon. In a previous study, Schizophrenia spectrum (SzSp) patients rated positive, negative and neutral stimuli that were multimodally presented, while assessed with a checklist exploring anomalous subjective experiences and evaluated for positive and negative symptomatology. In the present work, we aimed to further explore the relationship between neutral stimuli misperception, anomalous experiences and positive/negative symptoms in SzSp patients. To this end, we adopted a dimensional approach by reconstructing from available data: 1. four a priori scales representing essential dimensions of SzSp experiential pathology following Parnas and colleagues (2005) and 2. five clinically meaningful factors to describe illness severity derived by Toomey and colleagues (1997). Results showed that although overall patients correctly recognized the target emotions, those who misinterpreted neutral auditory cues as negatively valenced also presented higher scores in Perplexity, Bizarre Delusions and Disorganization dimensions. Moreover, a positive association between Bizarre Delusions and both Perplexity and Self-Disorder dimensions emerged, suggesting that psychotic symptoms may be directly linked to patients’ subjectivity. In an attempt to comprehensively capture the multilayered neutral stimuli misperception phenomenon in SzSp, we aimed at bridging phenomenology and neurobiology by tentatively connecting the levels of molecular neurochemistry (i.e. altered dopaminergic neurotransmission), system neuroscience (aberrant salience of perceptual details) and psychopathology (the chain involving hyper-reflexivity, self-disorders and the emergence of delusions).